2014
DOI: 10.3934/nhm.2014.9.519
|View full text |Cite
|
Sign up to set email alerts
|

An easy-to-use algorithm for simulating traffic flow on networks: Theoretical study

Abstract: Abstract. In this paper we study a model for traffic flow on networks based on a hyperbolic system of conservation laws with discontinuous flux. Each equation describes the density evolution of vehicles having a common path along the network. In this formulation the junctions disappear since each path is considered as a single uninterrupted road.We consider a Godunov-based approximation scheme for the system which is very easy to implement. Besides basic properties like the conservation of cars and positive bo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(50 citation statements)
references
References 26 publications
(90 reference statements)
0
50
0
Order By: Relevance
“…This approach differs from the one proposed in [8], which instead assigns a path to each microscopic vehicle through the network in the spirit of the multipath traffic model introduced in [3,4]. 6.2.…”
Section: Examples Of Junctionsmentioning
confidence: 99%
“…This approach differs from the one proposed in [8], which instead assigns a path to each microscopic vehicle through the network in the spirit of the multipath traffic model introduced in [3,4]. 6.2.…”
Section: Examples Of Junctionsmentioning
confidence: 99%
“…In this context let us mention the paper by Cristiani and Sahu [14] which investigates the many-particle limit of a first-order FtL model suitably extended to a road network. The corresponding macroscopic model appears to be the extension of the LWR model on networks introduced by Hilliges and Weidlich [32] and then extensively studied by Bretti et al [4] and Briani and Cristiani [6].…”
mentioning
confidence: 99%
“…In general, they all allow to determine a unique solution for the traffic evolution on the network, but the solutions might be different. In the following we will employ the approach (iii) together with a Godunov-based numerical approximation [4,5], also used to reproduce Wardrop equilibria [8]. More recently, it was shown that the solution computed by the path-based model coincides with the many-particle limit of the first-order microscopic follow-the-leader model [9].…”
mentioning
confidence: 99%
“…In Sec. 2 we present in detail the mathematical model, which is a local version of the path-based approach [4,5], suitable to deal with large networks. In Sec.…”
mentioning
confidence: 99%
See 1 more Smart Citation